The wealth ladder : proven strategies for every step of your financial life - Maggiulli, Nick (Portfolio/Penguin, 2025)
If you've been spinning your wheels trying to get ahead financially, working more hours, or chasing the latest financial trends, but still find yourself stuck, the problem might not be your work ethic, your boss, or even bad luck. The real issue is likely your approach. But what if there was a better way? A new framework for understanding how to build wealth that actually works -- not some get-rich-quick scheme or one-size-fits-all solution, but a philosophy that fundamentally changes how you think about money. Enter "The Wealth Ladder." This revolutionary system doesn't tell you what to do; it teaches you how to think about your finances. In a world where interest rates, careers, and desires are always shifting, why should your strategy for building wealth stay the same? It shouldn't. Instead, you need a solid framework that adapts with you throughout your financial journey. This book breaks down wealth into levels, each requiring a different strategy. What gets you from Level 1 to Level 2 is not the same strategy that will get you from Level 5 to Level 6. Throughout the book, you'll learn which strategies are best suited for each level, allowing you to tailor your approach as you climb higher. This framework will fundamentally change how you look at your finances, and the financial choices you make. Because the difference between those who build wealth and those who don't isn't just about hard work -- it's about following the right strategies and focusing time and energy where it matters most. With "The Wealth Ladder," you won't need to guess where to put your focus. The path to financial success is clear; the only question left is, are you ready to climb?